Navigating life when a loved one’s (euthanasia) death is near: A narrative interview study from the Netherlands - Bernadette Roest; Megan Milota; Carlo Leget (PLoS ONE, 2025)
In this article, we describe our empirical research that started out as an exploration of “family involvement” in the Dutch practice of euthanasia, in the broader context of end-of-life decision-making and care under guidance of GPs in the home-setting. Informed by care-ethical insights and narrative approaches to qualitative research, we performed an in-depth interview study with 18 close relatives of people with incurable metastasized cancer (9 prospective, 9 retrospective). We came to understand how relatives’ involvement—not only in euthanasia but in any mode of dying—cannot be separated from relatives’ efforts to navigate through many dimensions of life when the death of loved one is near. Relatives have to navigate different spaces, decision-dynamics and the unfolding of professional care, strong emotional experiences, and intimate relationships (“the I-you-we”). This study brought to the fore that relatives and patients first and foremost accompany each other on this journey. The role of the GP can be valuable but vulnerable, and relatives’ broader social network and other professionals can be of enormous importance. The results of this study invited us to shift our perspective: it is not family members who get involved in euthanasia as a primarily medical affair. Instead, medical professionals are taking part in the profoundly social-relational experience of death and dying within families, whether that entails euthanasia or not. With this shift of perspective, specific practical and ethical questions start to receive more attention, for example questions about the available support for both patients and relatives regardless of the mode of dying.